2004
DOI: 10.1137/s1064827503422233
|View full text |Cite
|
Sign up to set email alerts
|

The Ultra-Weak Variational Formulation for Elastic Wave Problems

Abstract: In this paper we investigate the feasibility of using the ultra weak variational formulation (UWVF) to solve the timeharmonic 3D elastic wave propagation problem. The UWVF is a non-polynomial volume based method that uses plane waves as basis functions which reduces the computational burden. More general, the UWVF is a special form of the discontinuous Galerkin method. As a model problem we consider plane wave propagation in a cubic domain. We shall show numerical results for the accuracy, conditioning and p-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 19 publications
1
91
0
Order By: Relevance
“…We shall give more details of their results later in this paper. Extensive numerical experiments by Cessenat and Després, as well as by others [12][13][14], shows that the method converges throughout the domain of computation. The main purpose of this paper is to prove global convergence of the UWVF applied to the Helmholtz equation in the case where the medium is not absorbing as is often the case for scattering calculations.…”
Section: Introductionmentioning
confidence: 70%
“…We shall give more details of their results later in this paper. Extensive numerical experiments by Cessenat and Després, as well as by others [12][13][14], shows that the method converges throughout the domain of computation. The main purpose of this paper is to prove global convergence of the UWVF applied to the Helmholtz equation in the case where the medium is not absorbing as is often the case for scattering calculations.…”
Section: Introductionmentioning
confidence: 70%
“…This time integration method results, however, in most test cases in a decrease of the discrete energy. Although not addressed in this article, the methodology is expected to apply to other cases, such as the generalized linear system of Huttunen et al [7] and the three-dimensional acoustic equations [2]. We plan to explore these applications in our future research.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that care must be taken of the form in which the discrete UWVF is solved. While the preconditioned form (13) has a lower condition number its accuracy starts to deteriorate before that of the unpreconditioned equation (12).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that despite the UWVF matrix system (13) having a condition number two orders lower than the unpreconditioned form (13), the accuracy of the solution of (13) deteriorates earlier than for (12). The reason for this is, however, most likely in the two step inversion of the UWVF equation used in (13).…”
Section: Wave Propagation In a Duct With Rigid Wallsmentioning
confidence: 99%
See 1 more Smart Citation